Rubber (Hevea brasiliensis) Seed shell Activated Carbon Preparation, Characterization and Antibacterial Activity Studies (Universitas Jenderal Soedirman, 2022)
In Thailand, the rubber tree is widely used as a source of natural rubber and their seeds have been found to be rich in oil production. The seed shell is the residue and not edible but abundantly available in the country. Therefore, the objective of this work was to prepare activated carbon (AC) from rubber seed shells. ACs were produced by chemical activation and their characteristics were investigated. The effects of activation temperature and chemical impregnation time in the agent were examined. Proximate analysis was investigated and the results were within the standard of AC. The adsorption capacity was demonstrated with BET, iodine, and methylene blue number. The best produced AC (700 °C of activation temperature and 24 h of impregnation time) provided the highest BET surface area, iodine and methylene blue number were 923 m2/g, 1,234±24 mg/g and 1,204±10 mg/g, respectively. FT-IR spectrum indicates the presence of oxygen and nitrogen containing surface functional groups such as -OH, -CH3, -CH2, C=C, C-O, and N-H groups. The microstructure of the produced ACs was examined by SEM and the results found that they are porosity. The antibacterial effect results were discovered to be also effective against E. coli and S. aureus after 3 h and 24 h of contact times, respectively. In addition, the prepared AC also provided many properties that are better than those obtained by the commercial AC. Finally, it can be concluded that, AC from rubber seed shell can be applied as a low cost and possible alternate adsorbent.